(untitled) (Global Journal of Medical Research, 2020)
Recently, many types of research have reported odors. There are several types of lits used for testing, but in Japan, there re odor sticks, open essences, T&T olfactometry, etc. This time, we report that we conducted an olfactory cognitive test using open essence on healthy 117 peoples (35 males and 83 females). The Open Essence (made by FUJIFILM) has the smell as same as the odor Stick Identification Test (OSIT-J). The aromas used in the open essence includes curry, perfume, Japanese cypress, India ink, menthol, rose, wood, stinkysocks/sweat, roasted garlic, condensed milk, gas for cooking and Japanese mandarin aromas. This 12 different kinds of perception is not necessarily culture-free; the Japanese version employed. Depending on the type of odor, that were difficult to understand and some that were easy to understand. The most will-recognized odor was the smell of Curry, and the most hard to understand odor was mandarin orange. In males, the highest cognitive odor was Curry, and the lowest odor was Stir-fried garlic. In females, the highest cognitive odor was Curry, and the lowest odor was mandarin orange. In the future, it will be necessary to perform olfactory cognitive ability by age, using open essence.